The effect of youtube video blogs (vlogs) on self-esteem and life satisfaction among female adolescents - Louise Anne A. Evangelista. 4 0 16; 5
ABSTRACT: This study aimed at finding out the effects of YouTube video blogs (vlogs) on self-esteem and life satisfaction. It also wants to determine whether there will be a difference on the scores before and after the treatment and a difference on scores of the experimental and control group . 30 selected female adolescent students from Emilio Aguinaldo College were chosen in the study through purposive sampling having 15 participants on the experimental group and 15 participants on the control group. Experimental method was used by the researcher with the pre-test and post-test test as research design. Experimental group was treated with watching blogs while control group continued with their regular YouTube use. For the statistical treatment, the T-test of the values were computed to know the differences between the two groups. The generated findings show that there was significant difference from the self-esteem scores during pre-treatment and post-treatment. Additionally, a significant difference on self-esteem scores of the experimental and control group were proven. Ion contrast to these, no significant between the results of life satisfaction from the group who underwent with the treatment from those who did not and no significant difference of the life satisfaction scores before and after the intervention. Awareness of how watching vlogs can possibly affect the behavior a person when it comes to self-evaluation is recommend.
Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2